Dehydrated hereditary stomatocytosis with transient perinatal ascites. Issue 5 (1st September 2003) - Basu, A P; Carey, P; Cynober, T; Chetty, M; Delaunay, J; Stewart, G W; Richmond, S
Abstract : The case is reported of a mother and baby with dehydrated hereditary stomatocytosis and perinatal ascites, an autosomal dominant condition not previously reported in Britain. Recognition is important for the management of pregnancy and for avoidance of splenectomy which, if performed, can predispose the patient to fatal thromboembolic events.